RECONSTRUCTION THE AUTHORITY OF CONSTITUTIONAL COURT ON IMPEACHMENT PROCESS OF PRESIDENT AND/OR VICE PRESIDENT IN INDONESIAN CONSTITUTIONAL SYSTEM - Hezron Sabar Rotua Tinambunan (Faculty of Law, Universitas Jenderal Soedirman, 2016)
In the process of impeachment, Constitutional Court has the obligation to give its judgement to House of Representatives’s opinion regarding allegation of violation by the President and/or Vice President. Constitutional Court checks and judges House of Representatives’s opinion on whether or not the President and/or Vice President works fulfill Article 7A of Constitution of Republic Indonesia 1945 (UUD NRI 1945). The inspection done by Constitutional Court is the judicial process whose decision is in the form of justisil. The result of this impeachment process heavily depends on the judgement of People's Consultative Assembly in its plenary meeting which is also a politics forum, where President and/or Vice President could be dismissed or not. Constitutional Court’s judgement does not apply to People's Consultative Assembly, hence, the difference of Constitutional Court and People's Consultative Assembly’s judgement in plenary meeting that is very political by its nature is very likely to happen. Involvement of Constitutional Court in the procss of impeachment is, of course, different in each country. It depends on governance system in that particular country, it also relies on how much authority that is given by Constitution to Constitutional Court in the process of impeachment itself.Keyword: Authority, Constitutional Court, Impeachment.